2012
DOI: 10.1186/1742-6405-9-20
|View full text |Cite
|
Sign up to set email alerts
|

High virologic response rate after second-line boosted protease inhibitor-based antiretroviral therapy regimens in children from a resource limited setting

Abstract: BackgroundLimited data exist for the efficacy of second-line antiretroviral therapy among children in resource limited settings. We assessed the virologic response to protease inhibitor-based ART after failing first-line non-nucleoside reverse transcriptase inhibitor (NNRTI)-based regimens.MethodsA retrospective chart review was conducted at 8 Thai sites of children who switched to PI –based regimens due to failure of NNRTI –based regimens. Primary endpoints were HIV RNA < 400 copies/ml and CD4 change over 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
(27 reference statements)
4
12
0
Order By: Relevance
“…Among patients who switched to second-line ART, an estimated 85% (95% CI [75-91]) remained continuously suppressed <400c/ml at 12 months and 73% (95% CI [62-82]) at 24 months after switch. These rates of suppression are comparable to recent reports from Thailand and Africa, where all patients initiated on a PIbased second line regimen [26][27][28] . Another study of paediatric response to second-line ART in South Africa showed significantly poorer VL suppression in children receiving NNRTI-based as opposed to PI-based second-line therapy 29 .…”
Section: Europe Pmc Funders Author Manuscriptssupporting
confidence: 75%
See 2 more Smart Citations
“…Among patients who switched to second-line ART, an estimated 85% (95% CI [75-91]) remained continuously suppressed <400c/ml at 12 months and 73% (95% CI [62-82]) at 24 months after switch. These rates of suppression are comparable to recent reports from Thailand and Africa, where all patients initiated on a PIbased second line regimen [26][27][28] . Another study of paediatric response to second-line ART in South Africa showed significantly poorer VL suppression in children receiving NNRTI-based as opposed to PI-based second-line therapy 29 .…”
Section: Europe Pmc Funders Author Manuscriptssupporting
confidence: 75%
“…The median age, viral load, CD4 count, and CD4% at VL rebound were 10·6 years [5·6-13·4], 3·6 log 10 c/ml [3·1-4·2], 550 cells/μl , and 24% [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], respectively, and three-quarters of children initiated on a NNRTI-based regimen. Fifty one (30%) had already experienced some ART modifications not meeting the definition of switch prior to VL rebound.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This second-line regimen is associated with a high rate of virological suppression and immune reconstitution after 24 months of follow-up in adults from Cambodia, response to second-line ART in children, 40 this is a major concern, particularly due to the need for life-long treatment and the limited available subsequent drugs, restricting treatment management in these RLS.…”
Section: Coetzer Et Almentioning
confidence: 99%
“…Previous studies have demonstrated that continuing to maintain FTC or 3TC in the backbone of the second line regimen (SLR) has similar activity to using regimens with at least 2 other active NRTIs; 6,7 several studies suggest that SLR with protease inhibitors (PI) may be more effective. 8,9 Several reports have suggested that failure of second line therapy after developing M184V is due more to non-adherence, and not primarily to virologic failure (VF), 7,10 and that even the initial failing regimen may be used if adherence is improved. The purpose of this study was to describe the occurrence of the M184V mutation in a single clinic setting over a period of 10 years; to examine second line therapy choices, regarding VS, time to VS, and VF following virologic suppression (VS).…”
Section: Introductionmentioning
confidence: 99%